1997
DOI: 10.1073/pnas.94.25.13524
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor mutations in Escherichia coli methionyl-tRNA formyltransferase: Role of a 16-amino acid insertion module in initiator tRNA recognition

Abstract: The specific formylation of initiator methionyl-tRNA by methionyl-tRNA formyltransferase (MTF; EC 2.1.2.9) is important for the initiation of protein synthesis in eubacteria and in eukaryotic organelles. The determinants for formylation in the tRNA are clustered mostly in the acceptor stem. As part of studies on the molecular mechanism of recognition of the initiator tRNA by MTF, we report here on the isolation and characterization of suppressor mutations in Escherichia coli MTF, which compensate for the formy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 44 publications
(50 reference statements)
2
35
0
Order By: Relevance
“…Ribosomal protein RpsB and Fmt, which catalyzes the reaction of formylation of initiator methionyltRNA, were up-regulated in respect to the exponential and stationary phases. Fmt was previously reported to be important for the initiation of protein synthesis (11,27). Induction of elongation factors FusA and Tuf was observed in relation to the stationary phase.…”
Section: Discussionmentioning
confidence: 81%
“…Ribosomal protein RpsB and Fmt, which catalyzes the reaction of formylation of initiator methionyltRNA, were up-regulated in respect to the exponential and stationary phases. Fmt was previously reported to be important for the initiation of protein synthesis (11,27). Induction of elongation factors FusA and Tuf was observed in relation to the stationary phase.…”
Section: Discussionmentioning
confidence: 81%
“…Formylation of initiator tRNA f Met was performed in parallel by adding N 10 -formyltetrahydrofolic acid (0.3 mM final) and purified histidine-tagged E. coli methionyl tRNA formyltransferase to the tRNA f Met aminoacylation reaction (Ramesh et al 1997). Aminoacylation reactions were stopped by the addition of sodium acetate (pH 5.2) to 300 mM and placed on ice.…”
Section: Aminoacylation Of Trnamentioning
confidence: 99%
“…We investigated the in vivo state of the cytoplasmic yeast initiator tRNA in cells expressing the six-His-tagged wild-type MTF and the R42L mutant MTF. Previous studies had shown that introduction of the polyhistidine tag does not affect the activity of MTF (44). The R42L mutant MTF is ϳ1,400-fold less active in formylation of the E. coli initiator tRNA (45,46) and is used as a negative control here.…”
Section: Resultsmentioning
confidence: 99%
“…The E. coli MTF gene was cloned in the yeast expression vector YEp352-GAL1 (37). The wild-type and mutant MTF genes were amplified by PCR with the plasmids pQE16FMTp and pQE16FMTpR42L (44,45) as templates and the oligonucleotides 5Ј-ATCGGATCCAAAAAAAA TGTCAGAATCACTACGTATTATT-3Ј containing a BamHI site as the forward primer and 5Ј-CTCAGCTAATTAAGCTTAGTG-3Ј containing a HindIII site as the reverse primer. The PCR products coding for MTF-six-His fusion proteins were digested with BamHI and HindIII and cloned into the respective sites of YEp352-GAL1 to obtain YEp.MTF WT (wild type) and YEp.MTF R42L.…”
mentioning
confidence: 99%